Brief counseling by pharmacists enhances the knowledge, perceptions, and compliance of first and second-trimester pregnant women consuming ferrous fumarate at Jetis Community Health Center of Yogyakarta - Nurul Kusumawardani; Endang Darmawan; Akrom Akrom; Sulistiari Retnowati (Pharmaciana, 2019)
In Indonesia, the prevalence of anemia during pregnancy increased from 37.1% in 2013 to 48.9% in 2018. It plays a significant part in elevated maternal mortality and perinatal rates. This research aimed to determine the influence of a brief counseling intervention by pharmacists based on the ‘5A’ strategy that had been modified to include the knowledge, perceptions, and compliance of pregnant women with the recommended consumption of ferrous fumarate as anemia treatment and prevention. It is a quasi-experimental study with a pretest-posttest control group design. The data were collected prospectively from December 2018 to February 2019. The sample consisted of 26 respondents, divided into a control group and an intervention group. Each group comprised 13 pregnant women in their first and second trimester (ranging from 12 to 27 weeks). The knowledge, perceptions, and compliance in each group were measured on the first day of visit (Day 1; pretest) and Day 31 (posttest) after the intervention. The results showed a significant difference in average scores between the pretest and posttest in the intervention group (p<0.001 for knowledge, perceptions, and compliance parameters) but an insignificant difference in the control group (p=0.185, p=0.366, and p=0.111, respectively). Score difference or improvement was determined from the relative risk (RR) values of the three parameters (4.55, 4.54, and 10.29, respectively, with p<0.50). As a conclusion, a brief counseling intervention based on the modified ‘5A’ strategy can enhance the knowledge, perceptions, and compliance of first and second-trimester pregnant women at Jetis Community Health Center with the proper consumption of Fe fumarate as an iron supplement.